A declining CD4 count and diagnosis of HIV-associated Hodgkin lymphoma: do prior clinical symptoms and laboratory abnormalities aid diagnosis? - Ravindra K Gupta; Michael Marks; Simon G Edwards; Katie Smith; Katie Fletcher; Siow-Ming Lee; Alan Ramsay; Andrew J Copas; Robert F Miller (PLoS ONE)
Background The incidence of Hodgkin lymphoma (HL) among HIV-infected individuals remains unchanged since the introduction of combination antiretroviral therapy (cART). Recent epidemiological data suggest that CD4 count decline over a year is associated with subsequent diagnosis of HL. In an era of economic austerity monitoring the efficacy of cART by CD4 counts may no longer be required where CD4 count>350 cells/µl and viral load is suppressed (<50 copies/ml). Methods We sought to establish among our HIV outpatient cohort whether a CD4 count decline prior to diagnosis of HL, whether any decline was greater than in patients without the diagnosis, and also whether other clinical or biochemical indices were reliably associated with the diagnosis. Results Twenty-nine patients with a diagnosis of HL were identified. Among 15 individuals on cART with viral load <50 copies/ml the change in CD4 over 12 months preceding diagnosis of HL was -82 cells/µl (95% CI -163 to -3; p = 0.04). Among 18 matched controls the mean change was +5 cells/µl, 95% CI -70 to 80, p = 0.89). The decline in CD4 over the previous 6-12 months was somewhat greater in cases than controls (mean difference in change -55 cells/µl, 95% CI -151 to 39; p = 0.25). In 26 (90%) patients B symptoms had been present for a median of three months (range one-12) before diagnosis of HL. Conclusions The CD4 count decline in the 12 months prior to diagnosis of Hodgkin lymphoma among HIV-infected individuals with VL<50 copies/ml on cART was not significantly different from that seen in other fully virologically suppressed individuals in receipt of cART and who did not develop HL. All those who developed HL had B symptoms and/or new palpable lymphadenopathy, suggesting that CD4 count monitoring if performed less frequently, or not at all, among those virologically suppressed individuals with CD4 counts >350 may not have delayed diagnosis.